Landscape concept and Ergani Landscape - Cagliyan, Aye; Durmus, Esen (Istanbul Univ, Fac Letters, Dept Geography, 2012)
In the study of Landscape concept and Ergani Landscape, it is said that geographic land as the smallest geographic units in geographical segment which has explicit characteristic in respect of natural and human characteristics. Landscape are the smallest geographic units which have integrity in natural and human characteristics, however they may differ from very small partially. Accordingly Ergani have the characteristics of both Eastern Anatolia and South-Eastern Anatolia Regions and the sub-landscape which forming the both landscape by the existence of crossing area feature. While the north part embodying the characteristics of Taurus landscape and Upper Firat (Euphrates) Region, the south part embodying the characteristics of both Diyarbakir Basin and Karacadag land with Dicle region. And with this aspect it has been required mainly examination of areas with these kind of characteristics. Ergani breakdowned prominently with either physical or human and economical characteristics. Maden uplands at north where rains near 700-800 mm seen, forest cover rooted, fruit growing in along walley and developed viticulture at slopes in response of narrow cultivated areas, rare populated area while the depression plains and Ergani and Bereketli plains which a follow-up of Diyarbakir Basin correspond to place at where dry and irrigated farming could be observerd with 500-600 mm rains with step formation, the number of habitation increasing. Karacadag basaltic plato is a area of at where there is stockbreeding activity burst into prominence different from north and middle lands. With all these species Turkey's administrative and geographic borders had coincided in many fields and it has been need to arise landscape etudes with increasing analysis about regions borders recently.
Keywords: Region; Landscape; Maden Mountains; Bereketli Depresion; Karacadag Basalt Plataeu